Challenges and Opportunities for Academic Parents During COVID-19 - Lantsoght, Eva O. L.; Tse Crepaldi, Yvonne; Tavares, Silvia G.; Leemans, Kathleen; Paig-Tran, E. W. Misty (Frontiers in Psychology, 2021)
Parents in academic careers face notable challenges that may go unrecognized by university management and/or policy makers. The COVID-19 pandemic has shed light on some of these challenges, as academic parents shifted to working from home while simultaneously caring for children . On the other hand, many parents found that the shift to working from home offered new opportunities such as working more flexible hours, development of digital skillsets and cloud environments, and increased involvement in the education of their children. In this article we explore the work-related challenges and opportunities experienced by academic parents as a result of the COVID-19 pandemic and offer potential long-term solutions for academic parents and their universities. We use the following methods: 1) a literature review focused on identifying the work-related challenges academic parents faced prior to the pandemic, as well as the impact of the pandemic on scientists and working parents and 2) administer a world-wide survey with the goal of identifying the challenges and opportunities associated with parenting and academic work through the COVID-19 lockdown (309 total responses; 113 fully complete). We draw lessons for moving forward as we shape a new normal. We conclude this work by offering significant solutions to help support academic parents now and in the future. Our aim is to offer university administrators, policy makers, and community service providers with ways to provide additional support for academic parents as well as provide tools for academic parents to learn successful strategies directly from their peers.